Auténtico, Second Edition, 2nd Edition - Rodriguez, Robert; Tapia, Andrés (Berrett-Koehler Publishers, 2021)
America has an urgent need for Latino and Latina executives. This book identifies a path to uplift and amplify their representation in leadership. Latinos and Latinas will account for a third of our workforce by 2050-yet they make up only 5 percent of senior roles in corporate America. Dr. Robert Rodriguez and Andrés T. Tapia call this low percentage of Latino and Latina corporate executives today the "5 percent Shame." Inspired by Price M. Cobbs's seminal work on the secrets of successful Black leaders, this book seeks to understand the impact on Latinos and Latinas of the external forces of conscious and unconscious biases and of the internal forces of whether to assimilate or double down on their cultural identities in their quest to get ahead. The second edition features a new foreword by Henry Cisneros, former secretary of the Department of Housing and Urban Development, as well as updated statistics and graphs to represent how America's career landscape for Latinos has and has not changed and how to ensure Latinos can rise to their fullest potential. Using insights from in-depth interviews with twenty highly successful boomer Latino and Latina executives and focus groups with dozens of Gen X and millennial leaders, the authors have captured lessons about how these individuals chose their career paths, addressed challenges, and seized opportunities. The discussions are interpreted through the lenses of the authors' different personal experiences as Latino leaders in corporate America and synthesized as a guide for future leaders.